Vocabulary Learning in Digital-Game Based Learning Using Sega Genesis Video Games - Jhon, Alex (Proceeding of International Conference on Teacher Training and Education, 2016)
Abstract:Â Â Â Â Â Â  Digital game is not only a tool of entertainment, but it can also be used in pedagogical setting, making it an interesting issue of unconventional technology-integrated learning experience. This research aims to explore the respondentsâ vocabulary learning which mainly focuses on the use of four Sega Genesis video games, within the Digital Game-Based Learning experience. The research was conducted in Binus University which the respondents were 75 non-English departmentsâ students whose BNEPT (Bina Nusantara English Proficiency Test) scores were â¥ 500. The instruments used were four Sega Genesis video games (ESWAT: City Under Siege, Dick Tracy, Stargate and Demolition Man) and a Keywords Vocabulary Assignment. The video games were the main instruments of the hypothesis whether DGBL could help the respondents to acquire or reproduce sets of vocabulary specifically based on each of the video game. The vocabulary assignment is in a form of keyword listing for each of the game, there are ten words or phrases for each of the game, ranging from character design, first level design and gameplay. In result, based on the analysis of the filtered ten keywords from each four video games, it is proven that by playing video games, such as the four Sega Genesis video games indeed helps the EFL learners to have certain sets of vocabulary.Â Keywords:Â Â Â  vocabulary learning, digital game-based learning, sega genesis, video game